Markers of oxidative stress and energy metabolism in the rat myocardium during physical exertion and during the introduc- tion of an antioxidant – 8-benzylaminotheophyllinyl -7-acetic acid hydrazide (C-3) - Ryzhenko, V. P.; Bukhtiyarova, N. V.; Levich, S. V.; Ryzhov, O. A.; Makyeyeva, L. V.; Риженко, Віктор Павлович; Бухтіярова, Ніна Вікторівна; Левіч, Сергій Вадимович; Рижов, Олексій Анатолійович; Макєєва, Людмила Валеріївна (Czech Republic: European Scientific Center Biologial Marker, 2019)
One of the tasks of modern pharmacology is the development and creation of remedies that not only increase physical endurance, but also are able to protect target organs (heart, brain, kidneys, etc.) from hypoxia [1,2,3]. A significant increase in physical activity leads to an imbalance between the energy supply of the myocardium and its metabolic needs, i.e. to working hypoxia. During this period, there is an increase in the production of reactive oxygen species (ROS) by the bioenergetic reactions of mitochondria [3,4,5,6]. Oxidative stress develops during insufficient activity of antioxidant systems and an excess of ROS.
Keywords: substance C3; Mildronate; working hypoxia; energy metabolism; oxidative stress